STRUKTUR HUKUM AL-RAHN (GADAI SYARIAH) DALAM REGULASI POJK DAN FATWA MUI - Maulani Salsabila; Adi Rosadi; Ending Solehudin (JSE: Jurnal Sharia Economica, 2025)
This article explores the legal framework of al-rahn (Islamic pawn) by emphasizing the integration between state regulations and religious decrees in Indonesia. The analysis focuses on the relationship POJK as a source of formal legal authority and the fatwa DSN-MUI as a normative reference rooted in Islamic principles. A qualitative approach is employed through library research, examining official documents such as POJK No. 31/POJK.05/2014 on Sharia Financing Products and DSN-MUI Fatwa No. 25/DSN-MUI/III/2002 on Rahn. The findings reveal that POJK provides legal certainty and an operational framework for Islamic financial institutions, while the DSN-MUI fatwa establishes non-negotiable sharia boundaries. Both instruments work in a complementary manner to establish a credible, just, and socially responsive Islamic pawn system tailored to the needs of Indonesia’s Muslim community.